Fenfluramine hydrochloride for the treatment of seizures in Dravet syndrome: a randomised, double-blind, placebo-controlled trial. Issue 10216 (21st December 2019) - Lagae, Lieven; Sullivan, Joseph; Knupp, Kelly; Laux, Linda; Polster, Tilman; Nikanorova, Marina; Devinsky, Orrin; Cross, J Helen; Guerrini, Renzo; Talwar, Dinesh; Miller, Ian; Farfel, Gail; et al.
Summary: Background: Dravet syndrome is a rare, treatment-resistant developmental epileptic encephalopathy characterised by multiple types of frequent, disabling seizures. Fenfluramine has been reported to have antiseizure activity in observational studies of photosensitive epilepsy and Dravet syndrome. The aim of the present study was to assess the efficacy and safety of fenfluramine in patients with Dravet syndrome. Methods: In this randomised, double-blind, placebo-controlled clinical trial, we enrolled children and young adults with Dravet syndrome. After a 6-week observation period to establish baseline monthly convulsive seizure frequency (MCSF; convulsive seizures were defined as hemiclonic, tonic, clonic, tonic-atonic, generalised tonic-clonic, and focal with clearly observable motor signs), patients were randomly assigned through an interactive web response system in a 1:1:1 ratio to placebo, fenfluramine 0·2 mg/kg per day, or fenfluramine 0·7 mg/kg per day, added to existing antiepileptic agents for 14 weeks. The primary outcome was the change in mean monthly frequency of convulsive seizures during the treatment period compared with baseline in the 0·7 mg/kg per day group versus placebo; 0·2 mg/kg per day versus placebo was assessed as a key secondary outcome. Analysis was by modified intention to treat. Safety analyses included all participants who received at least one dose of study medication. This trial is registered with ClinicalTrials.gov with two identical protocols NCT02682927 and NCT02826863 . Findings: Between Jan 15, 2016, and Aug 14, 2017, we assessed 173 patients, of whom 119 patients (mean age 9·0 years, 64 [54%] male) were randomly assigned to receive either fenfluramine 0·2 mg/kg per day (39), fenfluramine 0·7 mg/kg per day (40) or placebo (40). During treatment, the median reduction in seizure frequency was 74·9% in the fenfluramine 0·7 mg/kg group (from median 20·7 seizures per 28 days to 4·7 seizures per 28 days), 42·3% in the fenfluramine 0·2 mg/kg group (from median 17·5 seizures per 28 days to 12·6 per 28 days), and 19·2% in the placebo group (from median 27·3 per 28 days to 22·0 per 28 days). The study met its primary efficacy endpoint, with fenfluramine 0·7 mg/kg per day showing a 62·3% greater reduction in mean MCSF compared with placebo (95% CI 47·7–72·8, p<0·0001); fenfluramine 0·2 mg/kg per day showed a 32·4% reduction in mean MCSF compared with placebo (95% CI 6·2–52·3, p=0·0209). The most common adverse events (occurring in at least 10% of patients and more frequently in the fenfluramine groups) were decreased appetite, diarrhoea, fatigue, lethargy, somnolence, and decreased weight. Echocardiographic examinations revealed valve function within the normal physiological range in all patients during the trial and no signs of pulmonary arterial hypertension. Interpretation: In Dravet syndrome, fenfluramine provided significantly greater reduction in convulsive seizure frequency compared with placebo and was generally well tolerated, with no observed valvular heart disease or pulmonary arterial hypertension. Fenfluramine could be an important new treatment option for patients with Dravet syndrome. Funding: Zogenix.